Fanpower and Characters’Migration - Maria DICIEANU (E-REA)
We live in an age that favours character migration. The numerous platforms and online communities dedicated to fans of specific media products encourage people to unleash their creativity and produce content based on their favourite characters, occasionally even disregarding their initial context and designing for them alternative narratives or universes. Furthermore, the entire idea of transmedia narratives is based on the users’ shifting situations and individuals over several platforms. This paper aims to further investigate this phenomenon together with other instances in which the migration proved challenging. In addition, my study will look at other effects fandoms can have on character migration.